Analysis of mixed convection past a heated sphere. (June 2019) - Nath, Dipjyoti; Pati, Sukumar; Raju, B Hema Sundar
The hydrodynamic and thermal characteristics for laminar axisymmetric mixed convection from a heated sphere are analyzed numerically in this work. The governing transport equations of conservation of mass, momentum, and energy have been solved using a higher order compact scheme. The results are presented in terms of the distribution of the streamlines, isotherms, and vorticity contours, and local Nusselt number along the sphere surface together with drag coefficient and average Nusselt number. We identify critical Richardson number above which separation of flow is suppressed. It is revealed that the drag coefficient decreases with an increase in the Reynolds number (Re) and the decrease is more profound for lower range of Re . It is further revealed that the drag coefficient increases monotonically with an increase in the Richardson number, while the same decreases with the increase in the Prandtl number. The average Nusselt number increases monotonically with the increase in Reynolds number, Prandtl number, and Richardson number.